2001
DOI: 10.1046/j.1467-789x.2001.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

The biology of white adipocyte proliferation

Abstract: Expanded adipose tissue mass increases the risk for many clinical conditions including diabetes, hypertension, coronary atherosclerotic heart disease, and some forms of cancer. Therefore, it is imperative that we understand the mechanisms by which fat pads expand. The enlargement of fat cells during the development of obesity has been previously hypothesized to be a triggering factor for the proliferation of new fat cells. There is now a preponderance of evidence that adipose tissue is a source of growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
416
1
55

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 602 publications
(486 citation statements)
references
References 162 publications
(184 reference statements)
7
416
1
55
Order By: Relevance
“…Studies on rodents and humans showed that the body of a healthy, lean individual is composed of approximately 15-28 % fat mass (Avram et al 2005a) with low variance; however, a high-fat diet (HFD) induces obesity with a wide variability of fat mass accumulation as seen in some mouse genotypes (Moitra et al 1998;Hausman et al 2001;Koza et al 2006). Similarly, a wide range of phenotypes occur at the metabolic and functional levels in obese individuals, where excessive AT accumulation may lead to the metabolic syndrome (Kirkland 2013).…”
Section: Adipose Tissue and Obesitymentioning
confidence: 99%
“…Studies on rodents and humans showed that the body of a healthy, lean individual is composed of approximately 15-28 % fat mass (Avram et al 2005a) with low variance; however, a high-fat diet (HFD) induces obesity with a wide variability of fat mass accumulation as seen in some mouse genotypes (Moitra et al 1998;Hausman et al 2001;Koza et al 2006). Similarly, a wide range of phenotypes occur at the metabolic and functional levels in obese individuals, where excessive AT accumulation may lead to the metabolic syndrome (Kirkland 2013).…”
Section: Adipose Tissue and Obesitymentioning
confidence: 99%
“…Increased adiposity involves increases in fat-cell size and also new adipocyte formation through adipogenesis. 1,[5][6][7] Thus, a greater understanding of the molecular basis of adipogenesis may suggest rational therapeutic strategies aimed at manipulating adipocyte development as a means of treating disorders of adipose tissue mass.…”
Section: Introductionmentioning
confidence: 99%
“…However, much less is known about how adipose tissue becomes obese in adult animals. Because the number of adipocytes in a given fat mass increases in obesity (5), adipose tissue obesity is thought to depend on both hypertrophy of preexisting adipocytes and hyperplasia due to formation of new adipocytes from precursor cells (adipogenesis) (5)(6)(7). The adipose tissue stroma contains blood vessels and other cell types.…”
mentioning
confidence: 99%